QUALITATIVE ANALYSIS OF MUSLIM COMMUNITY'S PERCEPTION OF TAXES IN THE FRAMEWORK OF SHARIA ECONOMICS - Bambang Suryanto; Hosnie Siraj Saifoden; Umi Khulsum (Al Dzahab, 2024)
Purpose: This study aims to examine Muslim community conceptions of taxation from the perspective of Islamic economics and to understand how religious values influence perceptions and acceptance of taxation within Muslim-majority societies. Design/Methodology/Approach: This research employs a qualitative approach using a descriptive-interpretative method. The study was conducted within a Muslim community characterized by relatively high religiosity and active economic engagement. Informants were selected through purposive sampling based on their status as taxpayers and their experience in fulfilling zakat obligations. Data were collected through in-depth interviews, limited observations, and document analysis. The data were analyzed inductively through data reduction, thematic categorization, and interpretative conclusion drawing. E-Journal Al-Dzahab Vol. 05, Issue 02  September, 2024 Pages. 152-162     p-ISSN: 2808-7631 e-ISSN: 2808-758 Findings: The findings reveal that Muslim perceptions of taxation are shaped by the interaction of religious values, administrative experiences, fiscal literacy, and trust in government institutions. Taxation is conceptualized within three primary frameworks: as a financial burden, as an administrative obligation, and as a form of social contribution to public welfare. The main distinction between tax and zakat lies in normative legitimacy and spiritual dimension. Zakat is perceived as a religious obligation with eschatological implications, whereas taxation is understood as an institutional obligation within the modern state system. Nevertheless, most informants accept taxation as long as it is implemented based on the principles of justice, transparency, and public benefit in line with the objectives of maqāṣid al-sharī‘ah. Research Implications: These findings highlight the importance of strengthening both the moral and institutional legitimacy of fiscal policy. Enhancing value-based fiscal literacy and fostering collaboration between government institutions and religious authorities are essential to reinforce tax morale and encourage voluntary tax compliance among Muslim communities.